2012
DOI: 10.2478/v10265-012-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthropogenic pollution in river water based on the genetic diversity of Aeromonas hydrophila

Abstract: Aeromonas hydrophila is a valuable indicator of the quality of water polluted by sewage and pathogens that pose a risk for humans and cold-blooded animals, including fi sh. The main aim of this research was to evaluate anthropogenic pollution of river water based on genetic diversity of 82 A. hydrophila strains by means of RAPD, semi-random AP-PCR (ISJ) and the rep-BOX conservative repeats test. Genetic diversity of A. hydrophila was HT = 0.28 (SD = 0.02) for all DNA markers (RAPD, semi random and rep-BOX).Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The genus Aeromonas along with Pseudomonas and Vibrio are the predominant microorganisms in ponds and these bacteria may be used as good biological indicators of water quality (Rippey and Cabelli 1989;Korzekwa et al 2012). The number of Aeromonas bacteria inhabiting the water of three studied carp ponds varied from 1.93 to 2.96·10 2 CFU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Aeromonas along with Pseudomonas and Vibrio are the predominant microorganisms in ponds and these bacteria may be used as good biological indicators of water quality (Rippey and Cabelli 1989;Korzekwa et al 2012). The number of Aeromonas bacteria inhabiting the water of three studied carp ponds varied from 1.93 to 2.96·10 2 CFU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-three complete reports of these elements in Aeromonas isolates from different regions and sources have been describe between 2001 and 2023 at National Center for Biotechnology Information (NCBI) [5,. The detection of Aeromonas strains harboring integrons has been recorded in 34 countries on 5 continents (Figure 2); however, it is important to highlight that in some regions of Africa and Central America, there are no reports of the presence of integrons in these bacteria, despite the fact that both are indicators of fecal and anthropogenic contamination [112][113][114][115]. In fact, these areas are low-income countries where very few resources are available for research [116].…”
Section: Frequency and Distribution Of Integrons In Aeromonasmentioning
confidence: 99%
“…MAR phenomenon was clearly observed throughout the results. Supporting data from recent studies concluded the importance of taking proper measures to control MAR Aeromonads, particularly in water sources used by humans [62][63][64][65]. Antibiotic resistance leads to increase in the risk of inappropriate therapy as well as increase of bacterial transmission between humans due to long periods of infection [66,67].…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%